Intelligent fault prediction method of telecom system - Heng CAI; Lei GE (Dianxin kexue)
Some approaches based on deep learning would be used to analyze the process and port network on a server cluster.Specifically,the features of nodes were carefully selected in server cluster network,by combining the prior knowledge from actual operations,and the abnormal state of processes or ports on the cluster was predicted.According to the research,the running information such as loads of CPU and memory,communications between processes and the structural features in the process network was valuable in predicting the states of processes and ports; furthermore,the changes of features mentioned above in the time dimension reflected the states of processes or ports,too.